PHOTOTROPHIC PICOEUKARYOTES OF THE ONEGA BAY, THE WHITE SEA: ABUNDANCE AND SPEСIES COMPOSITION - T. A. Belevich; L. V. Ilyash; I. A. Milyutina; M. D. Logacheva; A. V. Troitsky; Т. А. Белевич; Л. В. Ильяш; И. А. Милютина; М. Д. Логачева; А. В. Троицкий (Lomonosov Moscow State University, School of Biology, 2017)
The abundance, biomass and species composition of phototrophic picoeukaryotes (PPE, cells size less than 3 μm) were studied in Onega Bay of the White Sea in June 2015. The highest PPE abundance and biomass were registered in the 0–5 m water layer. In the bay the average (in the 0–5 m water layer) abundance and biomass varied from 0 to 36,8 ·104 cell/l and from 0 to 117 μg С/m3, respectively. The Illumina sequencing of V4 region of 18S rRNA gene revealed eight classes of PPE. Mamiellophyceae dominated both in number of reads and operational taxonomic units. The green algae Bathycoccus prasinos, Ostreococcus tauri and Micromonas pusila, as well as diatoms Skeletonema marinoi and Minidiscus trioculatus were identified to species level. Численность, биомасса и состав фотоавтотрофных пикоэукариот (ФПЭ, размер клеток менее 3 мкм) оценены в Онежском заливе Белого моря в июне 2015 г. Наибольшие значения численности и биомассы ФПЭ были приурочены к слою 0–5 м, в котором средние значения этих показателей ФПЭ по акватории залива изменялись в пределах 0–36,8 ·104 кл/л и 0–117 мкг С/м3, соответственно. Метагеномное секвенирование области V4 гена 18S рРНК выявило присутствие таксонов ФПЭ, относящихся к восьми классам водорослей. По числу прочтений и операционных таксономических единиц преобладали Mamiellophyceae. До видового уровня идентифицированы зелёные водоросли Bathycoccus prasinos, Ostreococcus tauri и Micromonas pusila, а также диатомеи Skeletonema marinoi и Minidiscus trioculatus.